The safety, pharmacokinetics and neutralizing activity of recombinant human anti-rabies monoclonal antibody NM57 injection (rhRIG, Ormutivimab) in combination with rabies vaccination in Chinese healthy adults: A phase Ib randomized, double-blind, parallel-controlled clinical study - Yin Yin; Min Jia; Yufeng Li; Wei Zhao; Shuhong Chen; Peiyuan Huo; Qinghua Zhao; Lan Yu; Cha Wang; Yirui Ma; Meixia Wang; Jing Zhang (Travel Medicine and Infectious Disease)
Background: The combination of passive immune agents (human rabies immune globulin (HRIG) and equine rabies antiserum (ERA)) with vaccines are effective measures for preventing the onset of rabies post exposure. However, ERA and HRIG have potential risks of serum allergic reactions and blood-transmitted infectious diseases. This study compared the safety, pharmacokinetics and neutralizing activity of recombinant human anti-rabies monoclonal antibody NM57 injection (rhRIG, Ormutivimab) and HRIG in combination with rabies vaccine and vaccine alone. Method: This randomized, double-blind, parallel-controlled Phase Ib clinical study was conducted in healthy Chinese population to evaluate the safety, pharmacokinetics, and neutralizing activity of rhRIG at dosages of 20IU/kg and 40IU/kg in combination with vaccines, and to compare the neutralizing activity of rhRIG + vaccine with that of HRIG + vaccine and vaccine alone. 72 healthy participants divided into 6 groups of 12 individuals. Results: The rhRIG at dosages of 20IU/kg and 40IU/kg in combination with vaccines showed favorable safety and presented the pharmacokinetic property of linear elimination. The antibody neutralizing activity of rhRIG has the same level as HRIG in combination with vaccines. The rhRIG did not affect the long-term protective effect of the vaccine. Conclusions: The rhRIG could provide immediate immune protection at the wound site and producing earlier protection during the window period before the rabies vaccine established active immunity. Therefore, it is recommended to continue to evaluate the safety and antibody neutralizing activity of rhRIG (20 and 40IU/kg) in combination with the vaccine in Phase II clinical trials. Trials registration: ChiCTR1900023785 (https://www.chictr.org.cn).